GINS inactivation phenotypes reveal two pathways for chromatin association of replicative alpha and epsilon DNA polymerases in fission yeast. - Pai, C; García, I; Wang, S; Cotterill, S; Macneill, SA; Kearsey, S (2009)
The tetrameric GINS complex, consisting of Sld5-Psf1-Psf2-Psf3, plays an essential role in the initiation and elongation steps of eukaryotic DNA replication, although its biochemical function is unclear. Here we investigate the function of GINS in fission yeast, using fusion of Psf1 and Psf2 subunits to a steroid hormone-binding domain (HBD) to make GINS function conditional on the presence of beta-estradiol. We show that inactivation of Psf1-HBD causes a tight but rapidly reversible DNA replication arrest phenotype. Inactivation of Psf2-HBD similarly blocks premeiotic DNA replication and leads to loss of nuclear localization of another GINS subunit, Psf3. Inactivation of GINS has distinct effects on the replication origin association and chromatin binding of two of the replicative DNA polymerases. Inactivation of Psf1 leads to loss of chromatin binding of DNA polymerase epsilon, and Cdc45 is similarly affected. In contrast, chromatin association of the catalytic subunit of DNA polymerase alpha is not affected by defective GINS function. We suggest that GINS functions in a pathway that involves Cdc45 and is necessary for DNA polymerase epsilon chromatin binding, but that a separate pathway sets up the chromatin association of DNA polymerase alpha.